Counting 6to4 relay routers. - Malone, David
6to4 is a mechanism or providing IPv6 addresses and connectivity where native IPv6 is not available. In 6to4, the links between the IPv4 and IPv6 Internets are called relay routers These may be advertised publicly or privately. The number of 6to4 relay routers has been the subject of debate, as additional routers increase the scalability and efficency of the 6to4 system. Counting public relay routers is easy using the global routing table. This paper outlines a technique that can count private relay routers and reports results of applying this method. Our results indicate that there are a significant number of private relays in operation in comparison to the number of public relays. This number has increased over the last two years. The results also indicate that using distributed traceroute facilities to measure the multiplicity of an anycast deployment requires large numbers of nodes to be accurate
Keywords: Computer systems organization; Computer communication networks; Internetworking; Routers; Network protocols; IP; Performance of systems; Design; Management; Performance; Standardization; Theory